2013
DOI: 10.1111/ajt.12341
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes of Renal Transplant Recipients With Behavioral Adherence Contracts: A Randomized Controlled Trial

Abstract: The objective of this randomized controlled trial was to assess the effects of a 1-year behavioral contract intervention on immunosuppressant therapy (IST) adherence and healthcare utilizations and costs among adult renal transplant recipients (RTRs). The sample included adult RTRs who were at least 1 year posttransplant, taking tacrolimus or cyclosporine and served by a specialty pharmacy. Pharmacy refill records were used to measure adherence and monthly questionnaires were used to measure healthcare utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 40 publications
(59 reference statements)
2
105
0
2
Order By: Relevance
“…These educational and behavioral measures proved to be effective in a recent metaanalysis of studies on non-adherence, particularly when the strategies are combined [25]. Similarly, a recent prospective controlled study with randomized design that used a cognitive behavioral intervention achieved a reduction in nonadherence [13]. Others interventions like home visit, telephonic conversations, and self-improvement strategies were also effective in reducing non-adherence [14,16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These educational and behavioral measures proved to be effective in a recent metaanalysis of studies on non-adherence, particularly when the strategies are combined [25]. Similarly, a recent prospective controlled study with randomized design that used a cognitive behavioral intervention achieved a reduction in nonadherence [13]. Others interventions like home visit, telephonic conversations, and self-improvement strategies were also effective in reducing non-adherence [14,16].…”
Section: Discussionmentioning
confidence: 95%
“…The behavioral strategy involves a series of interactions between the patient and the healthcare professional, seeking an active participation of the patient in their treatment. Few prospective randomized studies have evaluated interventions to reduce non-adherence to immunosuppressants, in transplant recipients [12][13][14][15][16]. Therefore, this study aimed to assess the impact of an educational/counseling program highlighting the importance of immunosuppressive…”
Section: Introductionmentioning
confidence: 99%
“…Interventions, including improved long-term patient engagement and medication education have been demonstrated to improve adherence. Future efforts, including the use of technology and mobile applications may enhance the success of these proven pharmacist-led medication adherence interventions (21,22). Thus, the profession should work towards incorporation of the transplant pharmacist into the long-term ambulatory management of the transplant recipient as a predominant goal.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 A randomized controlled trial (RCT) of 150 adult renal transplant patients found that 1-year behavioral contract intervention significantly improved adherence to immunosuppressant therapy. 88 Table 3 highlights some patientlevel interventions for managing nonadherence to immunosuppressive regimens. 82,86 A recently presented RCT that tested the efficacy of a multidimensional, 6-month adherenceenhancing intervention in heart, lung, and liver transplant recipients showed a 16% increase in adherence at the end of the intervention period, an effect that persisted during the 6-month wean-off phase.…”
Section: Strategies For Managing Nonadherencementioning
confidence: 99%